CLOUD TECHNOLOGIES OF MONITORING OF THE QUALITY OF TRAINING OF WORKERS OF RAILWAY PROFILE - Tetyana Bondarenko; Olha Аgeeva (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
With the purpose of creating the system of monitoring of the quality of professional training of future workers of railway profile, the author puts forward a technology of using cloud services of the search system of Google. The article proves that the system provides a complex support of monitoring, from creating appropriate forms and storing of the results in cloud storage to the\processing of results of the monitoring and management of the system of testing on the basis of using the service of Google-Calendar. In the article there has been considered the usage of the concept of BYOD for testing of students' achievement. The article demonstrates the advantages of  the proposed approach to monitoring the quality of training of future workers of railway profile highlighting  the usage of the cloud services of the search system of Google as a means of  expanding the boundaries of research in space and time and making the procedure more flexible and systematic.